2017
DOI: 10.1007/s10812-017-0566-4
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Breakdown Spectroscopy Associated with Multivariate Analysis Applied to Discriminate Fertilizers of Different Nature

Abstract: A number of phosphate rocks and organomineral P fertilizers was analyzed comparatively by laser-induced breakdown spectroscopy (LIBS) in both single-and double-pulse modes associated with two chemometric methods, i.e., principal components analysis (PCA) and partial least squares regression (PLSR). PCA was demonstrated to be a valuable method for the identifi cation of spectral differences between similar samples with only minor compositional differences. The raw and normalized LIBS spectra were able to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…The authors detected several elements including Al, Ca, Cr, Cu, Fe, K, Mg, Mn, Na, Pb, Sr, and Zn, in two composts of different origin and four accumulator plant species (Atriplex halimus, Brassica alba, Brassica napus, and Eruca vesicaria). 103 They also verified their LIBS concentration results with ICP-OES measurements. These authors proved the feasibility of LIBS for fast elemental screening of plant and compost samples.…”
Section: Soil Compositional Analysis Using Libssupporting
confidence: 53%
“…The authors detected several elements including Al, Ca, Cr, Cu, Fe, K, Mg, Mn, Na, Pb, Sr, and Zn, in two composts of different origin and four accumulator plant species (Atriplex halimus, Brassica alba, Brassica napus, and Eruca vesicaria). 103 They also verified their LIBS concentration results with ICP-OES measurements. These authors proved the feasibility of LIBS for fast elemental screening of plant and compost samples.…”
Section: Soil Compositional Analysis Using Libssupporting
confidence: 53%
“…Normalmente, o primeiro passo para interpretação dos dados LIBS para um grande conjunto de amostras é a aplicação da PCA. [94][95][96][97][98][99][100] Outra abordagem quimiométrica muito empregada em análise por LIBS é o uso da calibração multivariada. Dentre as principais ferramentas de calibração multivariada aplicadas estão a partial least squares (PLS), 101 multiple linear regression (MLR), 65 artificial neural networks (ANN) 102 entre outras.…”
Section: Libs E Quimiometriaunclassified
“…Photonic techniques and machine learning algorithms have been extensively used to improve agricultural management in the past few years, mainly due to their high accuracy associated with their fast response, low analytical cost, simplified sample preparation, and environmentally clean techniques [ 7 , 8 , 9 , 10 , 11 , 12 ]. Recently, our research group demonstrated the potential application of the Fourier-transform infrared (FTIR) and Laser-induced breakdown spectroscopy (LIBS) for seed vigor classification [ 5 , 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%